THE EFFECT TRANSFORMATIONAL LEADERSHIP, PERSONALITY AND JOB PERFORMANCE ADMINISTRATION EMPLOYEE - Andinasari Andinasari; Bedjo Sujanto; Mukhneri Mukhtar (IJHCM (International Journal of Human Capital Management), 2017)
The purpose of this study was determine the effect transformational leadership, personality and job performance administration employeeUniversity of Indonesian Teachers Union of Palembang (PGRI). This research try answer problems about job performance involving of 144 administration employee had been selected from the target population of 223 employee by using quantitative approach with path analysis methods. The reseach of conclude show (1) transformational leadership had a direct effect positif on job performance; (2) Personality had a direct effect positif. Therefore to improve the job performance administration employee PGRI University of Palembang. Keywords:Transformational Leadership, Personality, Job Performance.